TANGGUNG JAWAB SEKUTU MAATSCHAP TERHADAP PIHAK KE 3 DALAM SUATU PERJANJIAN KONSORSIUM TERKAIT BUBARNYA MAATSCHAP ATAS KEHENDAK PARA SEKUTU (Kasus Perjanjian Konsorsium antara PT Agro Bintang Dharma Nusantara dengan Pemerintah Daerah Balikpapan, Bontang, K - Simorangkir, Julius Caesar Transon (FIAT JUSTISIA, 2015)
The development of society in the field of economy requires laws to regulate economic problems. Scientific developments in the field of economy should be accompanied by regulations that govern them. Dynamic human life resulted in a pattern of life that compound so that the interests of each individual is different, if not set or laid out by the law, there will be cheating in any transaction or trade activity. In the case of procurement of ferry quickly conducted a consortium of several regions in Borneo as Balikpapan, Bontang, Paser, and east Kutai PT Argo Stars Darma Nusantara in terms of cooperation agreements number 021/ABDN-Dir/SPK/X/01 dated October 4th, 2001, for the provision of services fast boats "water jet ferry" Trans East Kalimantan. Based on the above cases occur inequality allies in terms of responsibility to third parties, due to the dissolution of the consortium agreement by the will of some allies. Section 1646, Book IV of the Civil Code to determine the various ways the end of an alliance, one of which is the fellowship ended due to the will of one or several parties. The termination agreement also automatically terminates the agreement made by the parties. However, responsibility for third party does not necessarily come to an end. Responsibility towards third parties stipulated in Article 1642-1645.Keywords: Responsibility Allies, to third parties, the Consortium Agreement